Nurturing constructive change that works: a critical theory-informed model for transforming health service psychologists’ views of people with disabilities - Roy O. Gathercoal; Kathleen A. Gathercoal; Winston Seegobin; Sarah Hadley (Qualitative Research in Medicine & Healthcare)
We have been developing and refining a disability training exercise for health service psychologists that is ever more effective at encouraging lasting change in the way students regard disabilities and the people who live with those disabilities. Although research suggests that simulation exercises tend to be ineffective at creating long-term attitude change in participants, quantitative and qualitative results indicate our exercise, composed of a simulation followed by debriefing and reflection, helps professionals better understand some of the challenges people with disabilities daily face, and how those challenges can affect their well being. We found this combination is more likely to yield long-term changes than any of these approaches alone. This paper is not principally the description of a pedagogical technique, but instead is an examination of how the combination of simulation, debriefing, and reflective journaling may challenge taken-for-granted assumptions about disabilities, e.g., that disabilities transform individuals into a different kind of human being (with either superhuman powers or as object of pity) instead of seeing these individuals as ordinary people facing extraordinary, and often society-created obstacles. One frequent call of Critical Theorists is to challenge those things we take for granted. Social and cultural structures create specific viewpoints and thus problematizing the apparent is necessary for understanding of, and emancipation from, potentially oppressive social structures. Inspired by this call to render the taken-for-granted as problematic, the exercise we describe creates inversions of performer/audience, professional/student, and scientist/researcher positions. In each of these inversions, the role of the objective observer is denied and the student is invited to engage in his or her own evaluative and potentially transformative experience. Through each of these inversions, different realities can be more readily utilized by thoughtful students to render problematic some of the dominant views about people with disabilities. To make this case, we utilize both qualitative and quantitative methods. The students’ own words, captured in their journals before and after the exercise, are examined in comparison with program goals and features. The weight of the evidence is impressive, indicating that the combination of simulation, debriefing and journaling reflection are effective at creating a space in which change of attitudes does occur.